Too Many Bargainers Spoil The Broth: The Impact of Bargaining on Markets with Price Takers. - Gill, D; Thanassoulis, J (Department of Economics (University of Oxford), 2007)
In this paper we study how bargainers impact on markets in which …rms set a list price to sell to those consumers who take prices as given. The list price acts as an outside option for the bargainers, so the higher the list price, the more the …rms can extract from bargainers. We …nd that an increase in the proportion of consumers seeking to bargain can lower consumer surplus overall, even though new bargainers receive a lower price. The reason is that the list price for those who don't bargain and the bargained prices for those who were already bargaining rise: sellers have a greater incentive to make the bargainers'outside option less attractive, at a cost to pro…ts from non-bargainers. Competition Authority exhortations to bargain can therefore be misplaced. We also consider the implications for optimal seller bargaining.